Effectiveness of Role Playing Learning Method In Improving Speaking Skills Elementary School Students - Nur Oktavia Jasama, Venny Surya; Mahendra, Yasinta; Suprapto, Irawan (Scidac Plus, 2026)
Speaking skills are an important competency in Indonesian language learning in elementary schools because they play a role in developing communication skills, self-confidence, and active participation. However, various studies have shown that students' speaking skills have not developed optimally due to teacher-centered learning. This study aims to analyze the effectiveness of the role-playing learning method in improving elementary school students' speaking skills through a Systematic Literature Review (SLR) approach. Literature searches were conducted through the Google Scholar database between 2021 and 2025 using the keywords